Kenaikkan Harga BBM dan Dampaknya Terhadap Kepentingan Publik - M.Fhedry Chandriyadi; Nuzli Rhamadhani (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2026)
The policy of increasing fuel prices is a strategic public policy that has broad implications for the lives of people in Indonesia. Fuel plays an important role in supporting economic activity, distribution of goods, and social mobility. This article aims to analyze the impact of the fuel price increase policy on public interests by emphasizing the current context in Indonesia and the empirical realities that arise in society. This study uses a qualitative approach through literature review and policy analysis. The results of the study show that the increase in fuel prices has a direct impact on the increase in the cost of living, a decline in people's purchasing power, and the emergence of social pressure, especially among low-income groups. Although the government views this policy as a rational step to maintain fiscal stability and the sustainability of energy subsidies, compensation and social protection policies remain key factors in ensuring that the public interest and the goal of community welfare are maintained.